Investigating Deinococcus radiodurans RecA protein filament formation on dsDNA by a real-time single-molecule approach - Hsu, Hsin-Fang (2011)
With the aid of an efficient, precise, and almost error-free DNA repair system, Deinococcus radiodurans can survive hundreds of double strand breaks inflicted by high doses of irradiation or desiccation. The RecA of Deinococcus radiodurans (DrRecA) plays a central role both in the early phase of repair by an extended synthesis-dependent strand annealing process and in the later more general homologous recombination phase. Both roles likely require DrRecA filament formation on duplex DNA. We have developed single-molecule tethered particle motion (TPM) experiments to study the assembly dynamics of RecA proteins on individual duplex DNA molecules by observing changes in DNA tether length resulting from RecA binding. We demonstrate that DrRecA nucleation on dsDNA is much faster than Escherichia coli (Ec) RecA protein, but the extension is slower. This combination of attributes would tend to increase the number and decrease the length of DrRecA filaments relative to those of EcRecA, a feature that may reflect the requirement to repair hundreds of genomic double strand breaks concurrently in irradiated Deinococcus cells.